2014
DOI: 10.1080/09602011.2014.917686
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the experience of self in the social world for men following traumatic brain injury

Abstract: This study explores the lived experience of male survivors of traumatic brain injury (TBI) in relation to perceived changes in their personal and social identity. The aim was to provide an understanding of the individuals' sense of self and sources of emotional distress and growth following injury. Semi-structured interviews were conducted with nine male survivors of TBI (aged 22-59 years). These men were 17 months to 21 years post-injury and were recruited through a UK holistic neuropsychological rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…This finding brings together previous literature identifying that people with TBI report being positioned by others as being passive and dependent [53,54,76] and that acting independently is, therefore, central to rebuilding a positive identity [38] and living a productive life. [77] Participants in this study described that being independent was both an attribute, which they demonstrated through participation in decision making, and a goal.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This finding brings together previous literature identifying that people with TBI report being positioned by others as being passive and dependent [53,54,76] and that acting independently is, therefore, central to rebuilding a positive identity [38] and living a productive life. [77] Participants in this study described that being independent was both an attribute, which they demonstrated through participation in decision making, and a goal.…”
Section: Discussionsupporting
confidence: 57%
“…The number of participants in this study, while relatively small, is comparable with similar studies [6,38,40,41,53,54,101]. Further, undertaking multiple interviews with participants supported the generation of rich qualitative data, from which several key themes clearly emerged and the relationship between decision-making participation and self-conceptualization was developed.…”
Section: Methodological Considerations and Future Directionsmentioning
confidence: 58%
See 2 more Smart Citations
“…However, loss of communication skills for those with a significant TBI is common due to cognitive-communicative deficits, which can have wide-ranging consequences socially [13][14][15]18,23]. It is common for people with TBI to lose friends within the first year after injury and there are often notable difficulties after TBI in maintaining and building social networks [13,[23][24][25], including changing relationships and communication with family members [26][27][28]. Their ability to socialise and to build or maintain relationships is often greatly impaired [13,15,18].…”
Section: Injury (Tbi)mentioning
confidence: 99%